2022
DOI: 10.15376/biores.17.3.4816-4836
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the equilibrium moisture content and specific gravity of thermally modified wood via an Aquila optimization algorithm back-propagation neural network model

Abstract: The equilibrium moisture content and specific gravity of Uludag fir (Abies bornmüelleriana Mattf.) and hornbeam (Carpinus betulus L.) woods were investigated following heat treatment at different temperatures and times. Two prediction models were established based on the Aquila optimization algorithm back-propagation neural network model. To demonstrate the effectiveness and accuracy of the proposed model, it was compared with a tent sparrow search algorithm-back-propagation network model, a back-propagation n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…To further assess the IBWO-BP model's effectiveness in predicting the physical and mechanical properties of heat-treated wood, we conducted a comparison with previous studies. The comparative analysis model will be developed in four different models: the Aquila optimizer-BP model (AO-BP) [6], the nonlinear and adaptive grouping gray wolf optimisation-BP model (NAGGWO-BP) [29], a decision tree regression (DT) [49], and multiple linear regression (MLR) [50].…”
Section: Results Of Comparison Analysis With Earlier Prediction Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further assess the IBWO-BP model's effectiveness in predicting the physical and mechanical properties of heat-treated wood, we conducted a comparison with previous studies. The comparative analysis model will be developed in four different models: the Aquila optimizer-BP model (AO-BP) [6], the nonlinear and adaptive grouping gray wolf optimisation-BP model (NAGGWO-BP) [29], a decision tree regression (DT) [49], and multiple linear regression (MLR) [50].…”
Section: Results Of Comparison Analysis With Earlier Prediction Modelsmentioning
confidence: 99%
“…Among practical applications, BP neural networks can be used for tasks such as classification, regression, and clustering. It has also been widely used in wood science, for instance, to predict the EMC and SG [6] and the surface roughness [38] of wood.…”
Section: Bp Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [ 35 ] suggested two prediction models based on an AO algorithm and a back-propagation neural network model for estimating the equilibrium moisture level and precise gravity of thermally modified wood. The efficacy and accuracy of the suggested model were proved by comparison with two other models, as well as an ANN.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%